Kearifan Lokal dalam Pendidikan Kimia: Analisis Bibliometric - Islawati, Islawati (Lembaga Intelektual Muda (LIM) Maluku, 2025)
A bibliometric study provides a comprehensive mapping of a research field’s landscape and developmental trajectory. This article presents a bibliometric analysis of publications on local wisdom (local knowledge/ethnoscience/ethnochemistry) in chemistry education available on the ScienceDirect platform for the period 2014–2024. The initial dataset comprised 703 records; after screening based on predefined inclusion–exclusion criteria, 168 articles remained for analysis. The data analysis was limited to: (1) annual publication trends (number of documents), (2) the most productive authors based on publication counts, and (3) co-occurrence mapping of author keywords using VOSviewer. The results indicate an increase in publications after 2015, with emphasis on ethnoscience/ethnochemistry themes and cultural contexts such as batik as well as environmental practices. The co-occurrence map reveals thematic clusters consistent with the agenda of contextualising chemistry learning. These findings provide an empirical basis for formulating research agendas and developing local-wisdom-based instructional materials.